Anti-Bacterial Effects of Essential Oils against Uropathogenic Bacteria - Maria Loose; Emmelie Pilger; Florian Wagenlehner (MDPI AG, 2020)
Given the increasing antimicrobial resistance in urinary tract infections (UTI), alternative strategies need to be investigated. Determination of minimal inhibitory and bactericidal concentrations of essential oils from cajeput, lemongrass, tea tree, and thyme in artificial urine, revealed bactericidal activity of all four tested essential oils against seven uropathogenic species with values ranging between 0.78-50 mg/mL. Tea tree and thyme essential oils were more efficient than lemongrass and cajeput. In addition, antibiotic-resistant strains showed similar susceptibility as antibiotic-sensitive strains, suggesting no cross-resistance between antibiotics and these essential oils. Checkerboard assays revealed a synergistic activity of the combination of thyme and tea tree. Furthermore, the combination with thyme and tea tree essential oils increased the activity of fosfomycin and pivmecillinam, but not nitrofurantoin, against Escherichia coli. This study provides a basis for further investigation of the potential of thyme and tea tree oil as an alternative or additional treatment of UTI.